The Armed Neutrality Paradox: Sweden and Switzerland in US Cold War Armaments Policy. (April 2016) - Nilsson, Mikael; Wyss, Marco
This article presents the first comparative study of US policy towards two European neutrals, Sweden and Switzerland, in the late 1940s and early 1950s. During this period, Sweden and Switzerland were integrated into the Western security regime through a series of diplomatic, economic and technological steps until certain parts of the Swedish and Swiss armed forces were hard to separate from their NATO counterparts. This pioneering multi-archival study shows not only that US policy towards the neutrals was coordinated in order to make them conform to US security demands (a fact previously unnoticed by historians), but it also points towards another surprising and previously unknown conclusion – which the article calls 'the armed neutrality paradox'. The article argues that the transfers of military technology to Sweden and Switzerland, which were needed to make their neutrality credible, effectively undermined the very credibility that they were supposed to ensure. This technology became a conduit of foreign influence reaching straight into the nerve centre of the armed neutrals, and the more ubiquitous and advanced the technology got, the less control over its use the governments seemed to have. US policy, together with the efforts of the neutral governments to increase security, spawned this paradox.